(untitled) - Tohei, Koichi (New York, 1980)
By this book, the author presents the philosophical groundwork and specific disciplines by which the individual may attune himself or herself with the hi-life energy of the universe and thrive in health and harmony, without fatigue or depression
Keywords: Conduct of life,Hành vi cuộc sống,Spiritual exercises,Bài tập tinh thần